2013
DOI: 10.1128/cmr.00087-12
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Origin, Emergence, and Current Spread of a Successful Russian Clone of Mycobacterium tuberculosis

Abstract: SUMMARY Mycobacterium tuberculosis variant Beijing B0/W148 is regarded as a successful clone of M. tuberculosis that is widespread in the former Soviet Union and respective immigrant communities. Understanding the pathobiology and phylogeography of this notorious strain may help to clarify its origin and evolutionary history and the driving forces behind its emergence and current dissemination. I present the first review and analysis of all available d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 100 publications
4
88
2
6
Order By: Relevance
“…The 9-signal Beijing spoligotype profile was also predicted using in silico typing based on short sequence reads. A comparison of the MIRU-VNTR patterns with those of strains circulating in Russia (St. Petersburg Pasteur Institute database) and with strains from the MIRUVNTRplus.org database indicated that they corresponded to the 100-32 type (Beijing B0/W148) clonal cluster, previously defined as a successful Russian clone (18), and to the 94-32 cluster (1065-32 type), respectively, both of which are major Beijing groups found throughout the former Soviet Union (18-23).…”
Section: Resultsmentioning
confidence: 99%
“…The 9-signal Beijing spoligotype profile was also predicted using in silico typing based on short sequence reads. A comparison of the MIRU-VNTR patterns with those of strains circulating in Russia (St. Petersburg Pasteur Institute database) and with strains from the MIRUVNTRplus.org database indicated that they corresponded to the 100-32 type (Beijing B0/W148) clonal cluster, previously defined as a successful Russian clone (18), and to the 94-32 cluster (1065-32 type), respectively, both of which are major Beijing groups found throughout the former Soviet Union (18-23).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies evaluating dissemination of different phylogenetic groups of the Beijing M. tuberculosis family in different regions of the world demonstrated that the growing prevalence of Beijing TB is driven by strains of the modern sublineage, not ancient Beijing strains (5,17,18). These observations lead us to speculate that the supposed enhanced virulence and transmissibility, promoting dissemination of the Beijing strains, could be associated predominantly with strains of the modern sublineage.…”
mentioning
confidence: 84%
“…Напротив, в других странах Европы распространенность штаммов Beijing относительно невелика: Финляндия -5,2%, Швеция -5,8%, Польша -6,5%, причем их источники иные и более разнообразные, включая, в частности, штаммы, занесенные из Восточной Азии [6,11,24]. Известно, что на Северо-Западе России в по-пуляции M. tuberculosis генотипа Beijing широко представлены штаммы кластера В0/W148, ра-нее определенного как успешный российский вариант микобактерий туберкулеза [14]. Этот геновариант был впервые выявлен в середине-конце 1990-х гг.…”
Section: материалы и методыunclassified
“…Этот геновариант был впервые выявлен в середине-конце 1990-х гг. [4,13,23] и характеризуется зна-чимой ассоциацией с МЛУ и повышенной клас-теризацией (даже при сравнении с другими ва-риантами семейства Beijing) [14]. Была показана высокая способность штаммов B0/W148 к рас-пространению (трансмиссивность), в том числе описан случай нозокомиальной передачи [21].…”
Section: материалы и методыunclassified
See 1 more Smart Citation